Media for Embryo Culture of Some Tropical Recalcitrant Species. - Chin, Hoong Fong; Krishnapillay, Baskaran; Alang, Zaleha Christine (1988)
In this study, the excised embryos of 11 recalcitrant species were studied to determine suitable media and cultural conditions for their development into whole plants. Murashige and Skoog's medium formulation modified slightly by the addition of 0.17 gl-l NaH2P04 was found to be a suitable basal medium for all the species studied. The basal medium supplemented with 2 gl-l activated charcoal and 1.0 mgl- 1 NAA or IAA in combination with 1 mgl- 1 Kinetin, BAP or 2iP was found to be suitable for all the 11 species where the embryos developed normally to form whole plants. For some of the species, soaking the sterile excised embryos in an antioxidant (J 0 mgl- 1 ascorbic acid and 5 mgl- 1 citric acid) solution for 10-45 minutes prior to culture enhanced the normal development of embryos.